Unlocking Indonesia's Data Center Potential: Location Advantage and Cost Efficiency - Antonio Sebastian (Dinasti Publisher, 2024)
The data center industry is anticipated to grow significantly, with a projected 28% increase in demand by 2031. Indonesia is expected to play a major role in this expansion, with its potential IT workload demand for data centers predicted to hit 40% of the total regional IT workload in Southeast Asia. This study employs a descriptive-analytical (exploratory) method, comparatively analyze of Batam and Johor as potential Data Center location, using SWOT analysis and Scoring method with selection criteria matrix focusing on attributes, including subsea cable access, regional demand aggregation, renewable energy, and disaster resilience, alongside cost differences encompassing electricity, land, logistics, labor, and more. Results indicate that Batam generally outperforms Johor as a potential data center site, particularly considering the projected total data center market demand in Batam, reaching 311 MW by 2032, with 122 MW from local demand and 189 MW from spillover & returning demand from the regional market.